Experiences Administering Naloxone Among People in Different Social Roles: People Who Use Opioids and Family Members and Friends - Urmanche, Adelya A. (Journal of drug issues, 2023)
Unintentional drug overdose deaths continue to be a critical public health issue. Naloxone, a nonscheduled, safe, and effective drug that reverses opioid-involved overdoses is available to non-medically trained individuals (“lay people”), but there is scant information about how people in different social roles experience naloxone administration. We conducted 24 in-depth interviews with people who use opioids (PWUO; n = 15) and family members and friends of people who use opioids (FF; n = 9) who had administered naloxone in response to an opioid overdose. Compared with PWUO, members of the FF group were less reticent to administer naloxone in response to an overdose. PWUO and FF had different perspectives of law enforcement and demonstrated varied knowledge of the Good Samaritan Law. While PWUO found that having and administering naloxone was empowering, FF took a more pragmatic approach, reporting the need for naloxone as an unfortunate reality of their loved one’s drug use.